2022
DOI: 10.1002/erv.2956
|View full text |Cite
|
Sign up to set email alerts
|

Verbal memory following weight gain in adult patients with anorexia nervosa: A longitudinal study

Abstract: Background: Patients with Anorexia Nervosa (AN) show a moderate deficit in overall neuropsychological functioning. Since previous studies on memory performance mainly employed cross-sectional designs, the present study aims to investigate changes in verbal memory following weight-gain. Methods: Verbal memory was assessed with the Wechsler Memory Scale-Revised (WMS-R; 'logical memory'-story-recall-subtest) and the California Verbal Learning Test-II (CVLT-II; 'verbal learning'). Included were 31 female patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In adolescent patients (i.e., not adult study samples) with AN, some domains of cognitive functioning seem to improve with weight gain (Hatch, et al., 2010; Hemmingsen et al., 2021; Lozano‐Serra et al., 2014). It was also shown that in adult female patients, verbal memory was intact and logical memory improved (Terhoeven, et al., 2023). Similarly, our “trend” p ‐values in the longitudinal explorative analyses showing improvement in the AMT might also suggest that autobiographical memories associated with neutral or depression‐related experiences become more specific.…”
Section: Discussionmentioning
confidence: 98%
“…In adolescent patients (i.e., not adult study samples) with AN, some domains of cognitive functioning seem to improve with weight gain (Hatch, et al., 2010; Hemmingsen et al., 2021; Lozano‐Serra et al., 2014). It was also shown that in adult female patients, verbal memory was intact and logical memory improved (Terhoeven, et al., 2023). Similarly, our “trend” p ‐values in the longitudinal explorative analyses showing improvement in the AMT might also suggest that autobiographical memories associated with neutral or depression‐related experiences become more specific.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, one study found that biased episodic memory for negatively valenced information may help explain emotion regulation difficulties in AN (Manuel & Wade, 2013), suggesting that memory biases may underlie key affect regulation deficits in EDs. However, despite intriguing recent findings, tests of general episodic memory deficits have led to highly inconsistent results overall (Eneva et al, 2017; Keeler et al, 2022a; Stedal et al, 2021; Terhoeven et al, 2017; Terhoeven, Faschingbauer, et al, 2023; Weider et al, 2016).…”
Section: Back To the Future: Progressing Memory Research In Eating Di...mentioning
confidence: 99%
“…Most of the evidence points to people with AN producing fewer speci c AMs towards general (e.g., sorry, guilty, hopeless, worse, angry, hurt, lonely) or disorder-relevant cues (e.g., hunger, fat, judgement, weight, stigma. failure) than controls [8][9][10][11][12][13][14][15][16][17][18]. Episodic future thinking (EFT) is associated with the ability to recall speci c memories in line with the "constructive episodic simulation hypothesis", which posits that details from past events are exibly recombined to simulate novel future events [19].…”
Section: Introductionmentioning
confidence: 99%